TEACHER DEVELOPMENT FOR QUALITY OF LEARNERS IN THE 21st CENTURY - Narinto, Phrasamu Narit (Journal of Graduate MCU KhonKaen Campus, 2019)
The main objective of the study (1) to study the contexts of teacher development for quality of learners in the 21st century(2) to study the process of teacher development for quality of learners in the 21stcentury and (3) to present the teacher development for quality of learners in the 21stcentury. Research methodology was a mixed method research by mean of applying the qualitative research and qualitative research. The qualitative research was conducted by in-dept interview from the key informants before the focus group discussion for developing the completed model. The findings were conducted as follows: The contexts of teacher development for quality of learners in the 21st century mostlygot (=4.53)pointing that it was at highest level and when it was divided into the strategy founding that the fifth strategy (Supporting and developing the teachers ) getting (=4.62), the second strategy (The process of learning teaching being standard for learning in the 21st century) getting ( =4.53), the first strategy (Making the standard of teacher) getting ( =4.52) and the third strategy (Developing the teachers for having the skills of learning in the 21st century) getting ( =4.50) and the fourth strategy (Making the efficiency of teachers) getting ( =4.45) The process of teacher development for quality of learners in the 21stcentury mostlygot (=4.51)pointing that it was at highest level and when it was divided into the strategy founding that the fifth strategy (Supporting and developing the teachers ) getting (=4.64), the first strategy (Making the standard of teacher) getting( =4.52), the second strategy (The process of learning teaching being standard for learning in the 21st century) getting ( =4.51), and the third strategy (Developing the teachers for having the skills of learning in the 21st century) getting ( =4.48) and the fourth strategy (Making the efficiency of teachers) getting ( =4.41) The teacher development for quality of learners in the 21stcentury found that it should exam teacher permission certificate, make all teachers developing themselves every year, develop the system of salary, give the salary to the teacher suitably, measure the teachers’ work, and support for developing in the basic education.